Development of Google Sites-Based Guidebook through the RADEC Model Style Material to Improve Students' Critical Thinking - Marantika, Laura Oktaviany; Sari, Siti Mayang; Kasmini, Lili (Journal of Educational Sciences, 2025)
This study aims to develop a Google Sites-based guidebook through the RADEC (Read, Answer, Discuss, Explain, Create) learning model to improve the critical thinking skills of fourth grade elementary school students in science lessons. The background of this study is the low utilization of information technology in elementary education and the dominance of conventional learning methods that are centered on teachers. The RADEC model that emphasizes student activity and collaboration is considered effective if integrated with interactive digital media such as Google Sites. This study uses a Research and Development (R&D) approach based on the Borg & Gall model which includes the stages of problem identification, product development, limited and extensive trials, product revision, and final evaluation. Data were collected through expert validation sheets, teacher and student practicality questionnaires, and critical thinking tests. The results showed that the guidebook was classified as very valid with an average expert validation score above 85%. effectiveness on students' critical thinking skills, with an average N-Gain score of 0.5, which is categorized as moderate. The significance between the results of the Pretest and Posttest (p < 0.05), shows that Google Sites through the RADEC model has a positive impact on the development of students' critical thinking. Its implementation is suitable for elementary school students who have the potential to improve the quality of science learning and creative thinking. The Merdeka Curriculum emphasizes active, innovative, and technology-based learning.